GYY4137, as a slow-releasing H2S donor, ameliorates sodium deoxycholate–induced chronic intestinal barrier injury and gut microbiota dysbiosis - Pan, Shaorong; Yan, Han; Zhu, Jing; Ma, Yuanyuan; Wang, Pengyuan; Liu, Yucun; Chen, Zeyang (Frontiers in Pharmacology, 2024)
Introduction: Numerous studies have revealed that a long-term high-fat diet can raise intestinal deoxycholate acid concentration, which can harm intestinal mucosal barrier function in several ways. This study aims to verify the protective effect of GYY4137, as a slow-releasing H2S donor, on microbiome disturbance and the chronic injury of the intestinal mucosal barrier function caused by sodium deoxycholate.Methods: Caco-2 monolayer and mouse models were treated with a relatively high concentration of sodium deoxycholate (1.0 mM and 0.2%, respectively) for longer periods (32 h and 12 weeks, respectively) to understand the effects of GYY4137 on sodium deoxycholate-induced chronic intestinal barrier dysfunction and its fundamental mechanisms.Results: A relatively long period of sodium deoxycholate treatment can remarkably increase the intestinal barrier permeability, alter the distribution and expression of tight junction proteins and generate the production of pro-inflammatory cytokines (TNF-α and IL-1β) in the Caco-2 monolayers and mouse models. Moreover, it can activate the MLCK-P-MLC2 pathway in the Caco-2 monolayers, which was further confirmed using RNA sequencing. The body weight, intestinal barrier histological score, and TUNEL index of sodium deoxycholate-treated mice worsened. In addition, an induced microbiome imbalance was observed in these mice. The above variations can be reversed with the administration of GYY4137.This study demonstrates that GYY4137 ameliorates sodium deoxycholate-induced chronic intestinal barrier injury by restricting the MLCK-P-MLC2 pathway while elevating the expression level of tight junction proteins, anti-apoptosis and maintaining the microbiome's homeostasis.